Abiotic pathways of mercury methylation in the aquatic environment - Celo, Valbona (University of Ottawa (Canada), 2004)
This thesis studies the chemical reactions of mercury in different oxidations states with several natural methyl-donors present in the aquatic environment. The importance of the abiotic pathway of mercury methylation was assessed by a thorough examination of the kinetics of these reactions in various experimental conditions, relevant to environmental situations. The amount of methylmercury formed in the course of the chemical reactions studied herein shows that the abiotic mercury methylation can be a very significant source of this compound in the environment. The thesis comprises three main chapters which describe the reactions of three major methyl-donors: methyl iodide, methycobalamine and methyl tin compounds with mercury. Reaction of mercuric ions with methyl iodide yields HgI+ and HgI2 as inorganic products and MeOH as the only organic product. The reaction kinetics are biphasic and the reaction rate decreases with pH, increases with temperature and the reaction stops in the presence of complexing agents such as iodide ions. Meanwhile, the reaction of Hg0(aq) with methyl iodide yields 1.1% methylmercury which is a relatively high yield for environmental reactions. We show that the role of methyl iodide in the geochemical cycle of mercury in the aquatic environment is two-fold: it promotes the formation of compounds such as HgI + and HgI2 which are less reactive towards chemical and biological methylation and it methylates Hg0 which is present when Hg2+ is reduced by reducing agents found in the aquatic environment. The reaction of mercuric ions with methylcobalamine is studied using methylaquacobaloxime as a model compound. The mechanism is an electrophilic attack of Hg2+ to the Co-C bond. It results in the cleavage of this bond and formation of Hg-C bond in the structure of methyl mercury. The reaction is first order to mercury and methylcobaloxime concentration and the value of the second-order rate constant is k = (6.8 +/- 0.2) M-1 s-1 at 21.1°C, at a pH of 1.5 and an ionic strength of 0.030 M (HNO3). The reaction rate decreases with pH, and increases with temperature and ionic strength. The yield of methyl mercury formation is as high as 75%. The presence of chloride completely shuts down the reaction. So, abiotic methylation of mercury by methylcobalamin could be a source of methylmercury formation in fresh waters which have low pH and low chloride concentrations. (Abstract shortened by UMI.)
Keywords: Biogeochemistry.; Chemistry, General.